IDENTIFIKASI KESELAMATAN DAN KESEHATAN KERJA MELALUI INSTRUMEN SAFETY GAME PADA PERUSAHAAN HUTAN TANAMAN INDUSTRI PT. BUKIT BATU HUTANI ALAM DISTRIK MAKMUR KABUPATEN BENGKALIS - Kurnia Fitratunnisa; Evi Sribudiani; Sonia Somadona (JURNAL ILMU-ILMU KEHUTANAN, 2022)
Activities in the forestry sector is known as a sector that has a high safety risk. One of the activities in the forestry sector is the harvesting of timber forest. Where things are done at harvesting when not in accordance with SOP will cause a workplace accident. Forestry workers, especially timber harvesting, deserve occupational safety and health (OSH) guarantees. One of the efforts to increase OSH competence for workers in the field of forestry is felt quite attractive, effective, and efficient is to use the instrument safety game. The purpose of this research is to measure the increase in the knowledge aspects of field workers concerning OSH before and after given the instrument safety game and identify factors that affect the success of OSH knowledge improvement. To identify changes of increase in the respondent’s, use of the scoring results of the questionnaires are two types of questionnaires that is Self Assessment and Control Based Assessment to acquire the knowledge value of pre test, post test 1, and post Test 2 when trial using the safety game. The assessment using questionnaires showed an increase in knowledge after the use  instrument safety game. Based on the result of Wilxocon test, to increase knowledge from instrument safety game on contractor worker feeling manual using chainsaw after given 5 replay game increased from the enough category to be very good category